Effect of conjoint use of conventional and nano-fertilisers on growth, yield attributes and yield of Ethiopian mustard (Brassica carinata) in north-western Himalayas - KUMAR, ANSHUL; MANKOTIA, B S; BAJYA, NITIN; SAIN, DEERAJ (The Indian Journal of Agricultural Sciences, 2026)
Present study was conducted during winter (rabi) 2023-24 and 2024-25 at Experimental Farm of Shivalik Agricultural Research and Extension Centre, Chaudhary Sarwan Kumar Himachal Pradesh Krishi Vishvavidyalaya, Kangra, Himachal Pradesh. The experiment was laid out in factorial randomised block design to study the effect of three levels of RD-NP (recommended dose of nitrogen and phosphorus) viz., 100% recommended dose (RD)-NP, 75% RD-NP and 50% RD-NP and three sprays of nano-fertilizers viz. 2-sprays of nano-urea @ 4ml/litre at 25 and 45 DAS, 2 sprays of nano-DAP @ 4ml/litre at 25 and 45 DAS and 2 sprays of nano-urea + nano-DAP (4+4ml/litre) at 25 and 45 days after sowing (DAS) and one absolute control (water spray) in Ethiopian mustard (Brassica carinata A. Braun) variety “Jayanti” on growth, yield attributes and yield. The pooled analysis of two-year data represented that 100% RD-NP recorded significantly higher values of plant height, number of primary and secondary branches/plant, siliquae/plant (427.8), seeds/siliqua (12.6), seed yield (1778 kg/ha) and biological yield (7612 kg/ha) as compared to the treatments in which 75% RD-NP and 50% RD-NP was applied. Among nano fertilisers, 2 sprays of nano-urea + nano-DAP@ 4+4ml/litre recorded higher values of plant height (248.8 cm), number of primary and secondary branches/plant, siliquae/plant (409.6), seeds/siliqua (12.4), seed yield (1714 kg/ha) and biological yield (7271 kg/ha) than their individual application. The results indicated that foliar sprays of nano fertilisers showed positive influence on growth, yield attributes and yield in Ethiopian mustard. Thus, 2 sprays of nano-urea + nano-DAP @ 4+4ml/litre at 25 and 45 DAS with application of 60 kg N, 40 kg P2O5 and 40 kg K2O/ha is advisable in mid-hills of north-western Himalayas.